An Apos Investigation into Students’ Understanding of Logical Algebraic Connectives - Idowu Oluwaseun Longe; Aneshkumar Maharaj (Journal of Medives: Journal of Mathematics Education IKIP Veteran Semarang)
this research focused on understanding Applied Science students' abilities to correctly apply equality on connectives properties to algebraic logic expressions and to comprehend the students' schema. This was done by assessing the students’ understanding of mathematical logic connectors in light of the polytechnic’s curriculum and APOS theory. The students were taught using the conventional teaching method and computer-assisted instruction(CAI). Students were given a test with three theoretical questions. The APOS analysis determined the schema level. Students struggled to connect their understanding of truth tables to algebraic form, demonstrating challenges with connector properties (particularly de Morgan's) and errors in bracket applications, which are centered on students not having appropriate mental structure at the object and schema level. while correct precision and knowledge that mathematical symbolism serves both an instrumental role and a communicative function indicate some sort of schema.